Net photosynthetic and transpiration rates in a chlorophyll-deficient isoline of soybean under well-watered and drought conditions - Luquez, Virginia Martha Cristina (1997)
The gas exchange traits of wild type soybeans (cv. Clark) and a near-isogenic, chlorophyll-deficient line homozygous for the recessive allele y9 (y9y9) were compared under either well-watered or water-stress conditions. Mature leaves of y9 had a 65% lower chlorophyll content than wild type. However, the net photosynthetic rate (PN) of y9 leaves was only 20% lower than in the wild type, irrespective of water availability. Transpiration rates (E) were significantly higher in leaves of y9, compared to the wild type, either under well-watered or stress conditions. The higher E of y9 correlated with increased stomatal conductance, particularly in the abaxial epidermis, where more than 70% of the stomata were located. The combination of lower PN and increased E resulted in a significant decrease of water use efficiency in y9, at both water availability levels. The relative water content decreased in stressed leaves, much more in y9 than in wild type leaves, probably because of the higher E of the mutant line.